PENGARUH PEMODELAN SEDERHANA DALAM PEMBELAJARAN FISIKA BAGI MAHASISWA TEKNIK - Indri Dayana; Muhammad Fauzi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
research aims to determine the effect of simple modeling in learning physics for engineering students. The sample of this study were all 1st semester engineering students at the Medan Area University are 36. The research method used was the ex post facto method, by not providing treatment but directly conducting related evaluations. Engineering students' abilities in learning physics can be helped with simple modeling. Data analysis technique used is by regression analysis. From the results of the analysis it was found that Freghitung= 4.382 and Freg-table = 4.230 (Freg-count >Freg-table), so the conclusion of this study is that there is a very large the effect of simple modeling learning physics for engineering students at the University of Medan Area.